Pendampingan Strategi Promosi Media Sosial pada UMKM Krecek Rambak “UD Rengas Jaya” Mojoanyar Kabupaten Mojokerto - M.Syamsul Hidayat; Budi Utami; Eny Setyariningsih; Toto Heru Dwihandoko (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2024)
Social media is one of the main digital marketing strategies used to promote business products, with the aim of obtaining maximum profits (Hidayat et al., 2022). Social media and digital technology are gradually changing the way companies market their own products (Fraccastoro et al., 2021). However, there are still many MSMEs that do not use online sales optimally when marketing their products. Likewise, the MSME "Rengas Jaya" Mojokerto in carrying out its product marketing activities already uses digital technology. To overcome this problem, the Service Team of the Faculty of Economics, Majapahit Islamic University designed a solution by providing assistance in preparing a Digital Marketing strategy so that partners understand what a good marketing management strategy is by utilizing social media.This has an impact on increasing sales at the MSME "Rengas Jaya" address Mejero Village, Mojoanayar District, Mojokerto Regency. It is hoped that through digital marketing assistance it will have an effect on increasing their income. The results obtained from this activity for partners are: Partners understand the promotion strategy via social media. Then, by implementing the promotion strategy via social media, partners can increase the number of customers and increase sales.